Estudio teórico de las propiedades elásticas de los minerales Cu3TMSe4 (TM = V, Nb,Ta) por medio de cálculos atomísticos de primeros principios (2011)
ABSTRACT: The elastic properties of the family of isostructural minerals Cu3VSe4, Cu3NbSe4 and Cu3TaSe4 have been calculated for the first time using the state of the art in first-principles atomistic calculations, using Density Functional Theory and the Generalized Gradient Approximation for the exchangecorrelation energy functional. The elastic properties calculated are bulk modulus (B), the elastic constants (c11, c12 and c44), the Zener anisotropy factor (A), the isotropic shear modulus (G), the Young modulus (Y ), and the Poisson ratio (v). By means of these quantities we also computed other thermodynamic properties such as the average transversal (st) and longitudinal (sl) sound velocities and the Debye temperature (Teta D). The calculated values of B, c11, c12 and c44, G, Y and lead us to the conclusion that these compounds are compressible, fragile and brittle.